Mutations in the major gas vesicle protein GvpA and impacts on gas vesicle formation in Haloferax volcanii. Issue 4 (29th September 2017) - Knitsch, Regine; Schneefeld, Marie; Weitzel, Kerstin; Pfeifer, Felicitas
Summary: Gas vesicles are proteinaceous, gas‐filled nanostructures produced by some bacteria and archaea. The hydrophobic major structural protein GvpA forms the ribbed gas vesicle wall. An in‐silico 3D‐model of GvpA of the predicted coil‐α1‐β1‐β2‐α2‐coil structure is available and implies that the two β‐chains constitute the hydrophobic interior surface of the gas vesicle wall. To test the importance of individual amino acids in GvpA we performed 85 single substitutions and analyzed these variants in Haloferax volcanii ΔA + Amut transformants for their ability to form gas vesicles (Vac + phenotype). In most cases, an alanine substitution of a non‐polar residue did not abolish gas vesicle formation, but the replacement of single non‐polar by charged residues in β1 or β2 resulted in Vac – transformants. A replacement of residues near the β‐turn altered the spindle‐shape to a cylindrical morphology of the gas vesicles. Vac – transformants were also obtained with alanine substitutions of charged residues of helix α1 suggesting that these amino acids form salt‐bridges with another GvpA monomer. In helix α2, only the alanine substitution of His53 or Tyr54, led to Vac – transformants, whereas most other substitutions had no effect. We discuss our results in respect to the GvpA structure and data available from solid‐state NMR. Abstract : Gas vesicles are proteinaceous structures predominantly constituted by the gas vesicle protein GvpA forming the ribs of the gas vesicle wall. Single amino acid substitutions in GvpA either prevent gas vesicle formation in transformants, or lead to altered gas vesicle morphologies, i.e. tiny structures or cylinders instead of the spindle‐shaped gas vesicles of wild type. The results point out important amino acid positions in GvpA and support our in silico structural model of this protein.